Exploring Gender Inclusion in Industrial Engineering Classrooms - Puspandari, Dewi (Omnia Tempus, 2025)
This study explores gender inclusion in industrial engineering classrooms, aiming to identify the barriers, pedagogical practices, and institutional policies that affect the participation and success of female and gender-diverse students. The research employs a qualitative approach, specifically a literature review, to analyze existing studies and scholarly works related to gender dynamics in engineering education. Through a systematic collection of peer-reviewed articles, books, and other academic sources, the study synthesizes findings regarding the experiences of students in industrial engineering programs, focusing on factors such as implicit bias, stereotypes, lack of role models, and the overall classroom environment. The analysis reveals several key barriers to gender inclusion, including the perpetuation of male-dominated perceptions, biased faculty practices, and insufficient institutional support for gender diversity. Furthermore, the study highlights the critical role of faculty development in promoting gender-sensitive teaching practices and the importance of creating inclusive curricula and institutional policies that actively support gender-diverse students. The findings suggest that while progress has been made, continued efforts are necessary to create truly inclusive educational environments in industrial engineering. Key recommendations include the adoption of gender-sensitive pedagogies, the recruitment of female faculty members, and the establishment of support networks for female and gender-diverse students. These efforts are essential to ensuring that all students, regardless of gender, are given the tools and opportunities to succeed in the field.